2005
DOI: 10.1111/j.1471-4159.2004.02921.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterodimerization of opioid receptor‐like 1 and µ‐opioid receptors impairs the potency of µ receptor agonist

Abstract: Nociceptin activation of ORL1 (opioid receptor-like 1 receptor) has been shown to antagonize l receptor-mediated analgesia at the supraspinal level. ORL1 and l-opioid receptor (lR) are co-expressed in several subpopulations of CNS neurons involved in regulating pain transmission. The amino acid sequence of ORL1 also shares a high degree of homology with that of l receptor. Thus, it is hypothesized that ORL1 and lR interact to form the heterodimer and that ORL1/lR heterodimerization may be one molecular basis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 39 publications
4
56
1
Order By: Relevance
“…Second, there could be complexes of multiple receptors isolated with signaling molecules. Most of the G i/o -coupled receptors expressed in SH-SY5Y cells have been reported to heterodimerize with MOR, including DOR (George et al, 2000;Gomes et al, 2004), NOPr (Wang et al, 2005), ␣ 2 AR (Jordan et al, 2003), and CB 1 (Rios et al, 2006), whereas DOR has been shown to form heterodimers with ␣ 2 AR (Rios et al, 2004). In addition, preformed signaling complexes containing GPCR and multiple effectors have been identified (Davare et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, there could be complexes of multiple receptors isolated with signaling molecules. Most of the G i/o -coupled receptors expressed in SH-SY5Y cells have been reported to heterodimerize with MOR, including DOR (George et al, 2000;Gomes et al, 2004), NOPr (Wang et al, 2005), ␣ 2 AR (Jordan et al, 2003), and CB 1 (Rios et al, 2006), whereas DOR has been shown to form heterodimers with ␣ 2 AR (Rios et al, 2004). In addition, preformed signaling complexes containing GPCR and multiple effectors have been identified (Davare et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the probability of opioid receptor/G protein interaction is enhanced by compartmentalization in the membrane (Alt et al, 2001), allowing rapidity of GPCR signal propagation (Hur and Kim, 2002). Various modes of organization in the plasma membrane have been proposed to describe these compartments, including dimerization of receptors (George et al, 2000;Jordan et al, 2003;Gomes et al, 2004;Rios et al, 2004Rios et al, , 2006Wang et al, 2005), membrane microdomains (Allen et al, 2007), or protein scaffolds (Hall and Lefkowitz, 2002). However, mathematical modeling of experimental findings supporting compartmentalization has claimed that these data can be explained by a collision coupling model (Tolkovsky and Levitzki, 1978;Stickle and Barber, 1992) without the need to invoke compartments (Brinkerhoff et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, mechanisms of N/OFQ-mediated MOR desensitization also are cell, time, and signal pathway specific. Short-term N/OFQ pretreatment reduced the ability of the MOR agonists DAMGO (Mandyam et al, 2002;Wang et al, 2005) and morphine (Mandyam et al, 2000) to inhibit cAMP and to stimulate mitogen-activated protein kinase (Hawes et al, 1998). Acute desensitization of MOR responses by N/OFQ in BE(2)-C cells involves translocation of PKCa, GRK2, and GRK3 to the plasma membrane.…”
Section: Heterologous Regulation By N/ofqmentioning
confidence: 99%
“…Therefore, acute exposure to N/OFQ enhanced MOR-mediated homologous desensitization in BE(2)-C human neuroblastoma cells. The mechanism(s) by which acute N/OFQ-desensitized MOR responses in CHO and HEK cells were not investigated (Hawes et al, 1998;Wang et al, 2005).…”
Section: Heterologous Regulation By N/ofqmentioning
confidence: 99%
“…Heterodimerization can potentially play a role in the modulation of NOP or mu receptor activity by altering receptor-ligand interactions, functional activity of the respective receptors, and receptor trafficking. NOP/mu receptor heterodimers have been demonstrated using coimmunoprecipitation (Pan et al, 2002;Wang et al, 2005;Evans et al, 2010) and immunofluorescence microscopy approaches (Evans et al, 2010). Pan et al (2002) reported a very large (250 fold) increase in the affinity of mu agonists, but not naloxone, for the inhibition of [ 3 H]N/OFQ binding in cells transfected with both receptors.…”
Section: Cross Talk With Mu Opioid Receptorsmentioning
confidence: 99%